2007
DOI: 10.1111/j.1528-1167.2007.01055.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Wnt Inhibitor, Dickkopf‐1, Is Associated with Neurodegeneration Related to Temporal Lobe Epilepsy

Abstract: Summary:  Inhibition of the Wnt pathway by the secreted glycoprotein, Dickkopf‐1 (Dkk‐1) has been related to processes of excitotoxic and ischemic neuronal death. We now report that Dkk‐1 is induced in neurons of the rat olfactory cortex and hippocampus degenerating in response to seizures produced by systemic injection of kainate (12 mg/kg, i.p.). There was a tight correlation between Dkk‐1 expression and neuronal death in both regions, as shown by the different expression profiles in animals classified as “h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
97
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 40 publications
1
97
2
Order By: Relevance
“…In our system, Dkk1 reversibly affects the number of synapses without affecting programmed cell death. Interestingly, previous studies have indicated that increased Dkk1 levels contribute to cell death in cerebral ischemia (Cappuccio et al, 2005;Mastroiacovo et al, 2009), epilepsy (Busceti et al, 2007) and neurodegenerative diseases (Scali et al, 2006;Rosi et al, 2010). This apparent discrepancy could be explained by the low level and short-term treatment with Dkk1 used in our system.…”
Section: Discussioncontrasting
confidence: 41%
“…In our system, Dkk1 reversibly affects the number of synapses without affecting programmed cell death. Interestingly, previous studies have indicated that increased Dkk1 levels contribute to cell death in cerebral ischemia (Cappuccio et al, 2005;Mastroiacovo et al, 2009), epilepsy (Busceti et al, 2007) and neurodegenerative diseases (Scali et al, 2006;Rosi et al, 2010). This apparent discrepancy could be explained by the low level and short-term treatment with Dkk1 used in our system.…”
Section: Discussioncontrasting
confidence: 41%
“…Lithium is a compound used as a mood stabilizer, which is neuroprotective in a variety of disease models (12,13), such as brain ischemia (14) and kainate toxicity (15). The ability of lithium to promote autophagy, through the inhibition of the inositol-monophosphatase 1 (16)(17)(18), together with the protective effects of autophagy in neurodegeneration (19 -22), prompted us to test the neuroprotective effects of lithium in the G93A ALS mouse model.…”
mentioning
confidence: 99%
“…A growing body of evidence shows that inhibition of the canonical Wnt pathway contributes to the pathophysiology of neuronal damage in model of acute and chronic neurodegenerative disorders (De Ferrari and Inestrosa, 2000;Garrido et al, 2002;Inestrosa et al, 2002;Caricasole et al, 2003Caricasole et al, , 2004De Ferrari et al, 2003;Cappuccio et al, 2005;Scali et al, 2006;Busceti et al, 2007). Wnts are members of a family of secreted glycoproteins that regulate neuronal homeostasis during development, as well as in the adult life (Dale, 1998).…”
Section: Introductionmentioning
confidence: 99%